Successful treatment of multicentric Castleman's disease accompanying myeloma with bortezomib. (20th December 2012) - Khan, Afaq Ahmad; Siraj, Fouzia; Bhargava, Manorama; Aggarwal, Shyam
Abstract : Castleman's disease represents an atypical lymphoproliferative disorder which is non-clonal but can turn malignant in the form of lymphoma, Kaposi's sarcoma or plasma cell dyscrasia. It has been reported in association with diseases like polyneuropathy organomegaly endocrinopathy monoclonal gammopathy skin changes syndrome and myeloma and very rarely it can be associated with cutaneous vasculitis as in our case. It relatively runs an aggressive course and has a shorter survival. No standard of care therapy is yet established for multicentric Castleman's disease accompanying myeloma. We successfully treated one such patient with bortezomib-based therapy.